For a Voice and the Vote : My Journey with the Mississippi Freedom Democratic Party. - Todd, Lisa Anderson (Civil rights and the struggle for Black equality in the twentieth century., 2014)
"During the summer of 1964, more than a thousand individuals descended on Mississippi to help the state's African American citizens register to vote. Student organizers, volunteers, and community members canvassed Black neighborhoods to organize the Mississippi Freedom Democratic Party (MFDP), a group that sought to give a voice to Black Mississippians and demonstrate their will to vote in the face of terror and intimidation. In For a Voice and the Vote, author Lisa Anderson Todd gives a fascinating insider's account of her experience volunteering in Greenville, Mississippi, during Freedom Summer, when she participated in assembling the MFDP. Innovative and integrated, the party worked to provide education, candidates, and local and statewide organization for blacks who were denied the vote. For Todd, it was an exciting, dangerous, and life-changing experience. The summer culminated with the 1964 Atlantic City Democratic Convention, where the MFDP fought boldly for the opportunity to be included as the voting Mississippi delegation but, when they ultimately refused the Democrats' unacceptable terms, were criticized as politically naïve, militant protestors. This firsthand account attempts to set the record straight about the MFDP's challenge to the convention and to shed light on the efforts of this dedicated, loyal, and courageous delegation. Offering the first full account of the group's five days in Atlantic City, For a Voice and the Vote draws on oral histories, the author's personal interviews of individuals who supported the MFDP in 1964, and other primary sources"--Provided by publisher.